الذاكرة الدلالية عند الطفل المعاق سمعيا دراسة الميدانية بمدرسة الأطفال المعوقين سمعيا بالمسيلة الشهيد: رحماني نجاعي. - حاج حفصي اسراء; راجع امينة; بطاش لينة (جامعة المسيلة كلية العلوم الانسانية والاجتماعية, 2026)
هدفت الدراسة الحالية الى معرفة مستوىالذاكرةالدلالية وبنودها الخمس وذلك لدى الاطفال المعاقين سمعيا في ولاية المسيلة. وقد استخدمت الباحثات منهج دراسة الحالة في هذه الدراسة من اجل الوصف الاوضح والادق للعينة. تكونت عينة الدراسة من ثلاث حالات من تلاميذ مدرسة الأطفال المعاقين سمعيا، تم الاختيار العينة بطريقة عشوائية، تم استخدام الادوات التالية لجمع المعلومات: المقابلة العيادية، مقياس تقييم الذاكرة الدلالية لياسين لعجال لتحقيق اهداف الدراسة. نتائج الدراسة: - مستوى الذاكرة الدلالية لدى الطفل المعاق سمعيا في ولاية المسيلة مرتفع. - التلميذ يملك قدرة مرتفعة على فرز الكلمات الدلالية بشكل صحيح. - مستوى الطفل المعاق سمعيا على الفهم والربط الدلالي مرتفع. الكلمات المفتاحية:الذاكرة، الذاكرة الدلالية، الطفل المعاق سمعيا. Abstract : The current study aimed to identify the level of semantic memory and its five items among hearing-impaired children in M'Sila province. The researchers used the case study approach in this study for a clearer and more accurate description of the sample. The study sample consisted of three cases of students from a school for hearing-impaired children. The sample was selected randomly. The following tools were used to collect information: clinical interview، Yassin Lajjal's semantic memory assessment scale to achieve the study objectives. Study Results : -The level of semantic memory among hearing-impaired children in M'Sila province is high. .-The student has a high ability to correctly sort semantic words -The level of comprehension and semantic association among hearing-impaired children is high. Keywords: Memory، semantic memory، hearing-impaired children، hearing impairment.